Meta-terror: o uso da metalinguagem como recurso narrativo no slasher movie - Marchi, Marcelo Eduardo (2020)
Slasher movies - horror films characterized by the well-known premise of the serial killer that terrifies a group of young people, such as The Texas chainsaw massacre, Halloween, Friday the 13th and A nightmare on Elm Street - were a tremendous success with audiences during the first half of the 1980s. However, after that peak, the subgenre went into clear decay, since the exhaustive repetition of its formula ended up saturating viewers. Interestingly, in the mid1990s, it was the self-reflexive use of that same formula that ended up revitalizing it: premiered in 1996, Scream achieved a huge box office, became a landmark in popular culture and gave rise to an unexpected trend of slasher movies investing on metacinema. With daring and creative films like Behind the mask: the rise of Leslie Vernon and The cabin in the woods, the post-Scream era of horror movies has left us a rich field of study regarding the use of metacinema as a narrative resource and the ability to reinvent a subgenre through its own limitations. Thus, this research seeks to carry out a historiographical synthesis of the slasher movie based on the works of authors such as Carol J. Clover, Adam Rockoff, Richard Nowell, Jim Harper, and John Kenneth Muir, with the main focus on the elements of metacinema that have been found since the beginnings of the subgenre, but which gained strength especially with the release of Scream. Based on this and in a deep film analysis of selected works, it will be possible to understand the particular way in which each film used these elements, as well as the role of metacinema in reviving the slasher and in the process of making its formula increasingly dynamic.